Studi Literatur Tentang Agency Theory - Bambang Lesmono; Saparuddin Siregar (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
This study examines research with the keywords "earnings management" and principal and agent and "Agency Theory". This study uses descriptive statistical analysis and narrative review. In 2021 there will be 845 articles published and indexed nationally and internationally related to these keywords. After further review, not all articles are relevant and there are articles that cannot be accessed. Of the 845 articles, after further review, there are articles in the form of theses, theses, proceedings and books which in this study are excepted, so that only 497 articles are left. Meanwhile, the sample in this study was only 100 articles. In general, out of 100 published articles using a quantitative approach, 94 articles (94%) were published and articles published with a qualitative approach (6%). In this study, more were related to Earnings Management with 41 articles (41%), followed by corporate governance with 32 articles (32%). The two research themes were the most with other themes such as audits which only had 9 articles (9%), financial report reports with 5 articles (5%) and others with 13 articles (13%).